Comprehensive chromosomal and mitochondrial copy number profiling in human IVF embryos. Issue 1 (January 2018) - Shang, Wei; Zhang, Yunshan; Shu, Mingming; Wang, Weizhou; Ren, Likun; Chen, Fu; Shao, Lin; Lu, Sijia; Bo, Shiping; Ma, Shujie; Gao, Yumei
Abstract: Single cell whole genome sequencing helps to decipher the genome heterogeneity within a cell population and facilitates the analysis of trace amounts of genetic material, such as is found in human embryos. The mitochondrial genome, although an important part of the genetic composition of eukaryotic cells, is often neglected in single cell genome analysis. A recently developed single cell whole genome amplification method was used, known as multiple annealing and looping based amplification cycles (MALBAC-NGS), for simultaneous analysis of chromosomal and mitochondrial genomes at the single cell level. The platform was validated by a series of technical and biological replicates and used for chromosomal and mitochondrial copy number analysis in 399 in-vitro fertilized embryos from 81 couples. A positive correlation of maternal age with increased mitochondria quantity (β = 0.176, P = 0.001) was observed after adjusting for the impact of cell type. Lower numbers of mitochondria were detected in successfully implanted embryos, although the difference was not significant. It is proposed that MALBAC-NGS could potentially be used for an advanced pre-implantation genetic screening procedure with both chromosomal constitution and mitochondrial copy number being evaluated.